2016
DOI: 10.1186/s13395-016-0111-9
|View full text |Cite
|
Sign up to set email alerts
|

Muscle PGC-1α modulates satellite cell number and proliferation by remodeling the stem cell niche

Abstract: BackgroundThe myogenic capacity of satellite cells (SCs), adult muscle stem cells, is influenced by aging, exercise, and other factors. In skeletal muscle, the peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) is a key regulator of oxidative metabolism and endurance training adaptation. However, a link between PGC-1α and SC behavior remains unexplored.MethodsWe have now studied SC function in a PGC-1α fiber-specific gain-of-function animal model.ResultsIn surprising contrast to bona fide exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Importantly, even though a strong anti-inflammatory pattern of cytokine expression representing an M2-type polarization is observed, the less robust increase in M1, pro-inflammatory cytokine suggests that muscle PGC-1α could generally prime macrophages for rapid action, in which an M1 to M2 transition has to be tightly orchestrated to ensure proper repair and regeneration. An increased regenerative capacity in muscles overexpressing PGC-1α has recently been postulated15. We have shown that in addition to the increase of PGC-1α expression immediately and 4 h post-exercise, the expression of several chemokines and cytokines was also elevated 0 h and 4 h after exercise.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Importantly, even though a strong anti-inflammatory pattern of cytokine expression representing an M2-type polarization is observed, the less robust increase in M1, pro-inflammatory cytokine suggests that muscle PGC-1α could generally prime macrophages for rapid action, in which an M1 to M2 transition has to be tightly orchestrated to ensure proper repair and regeneration. An increased regenerative capacity in muscles overexpressing PGC-1α has recently been postulated15. We have shown that in addition to the increase of PGC-1α expression immediately and 4 h post-exercise, the expression of several chemokines and cytokines was also elevated 0 h and 4 h after exercise.…”
Section: Discussionmentioning
confidence: 55%
“…Muscle PGC-1α could thereby be indicative of the higher resistance of trained muscle fibers against damage and the more efficient repair and regeneration process1819 in a physiological context with consistently elevated PGC-1α gene expression. Indeed, the higher proliferative rate of satellite cells in MCKα mice further supports this hypothesis15. However, the exact chain of events will have to be elucidated in a temporal analysis in animal models in vivo after acute exercise and chronic training that both reflect the pulsatile induction of PGC-1α after each exercise bout and the persistent increase in basal PGC-1α expression linked to the fiber-type switch after prolonged endurance training20.…”
Section: Discussionmentioning
confidence: 90%
“…Considering the selective attenuation of extrasynaptic utrophin in the Sol muscles of MKO animals and the significant mitochondrial defects in MKO mice (38), it is likely that this translocation of PGC‐1α to the membrane represents a cellular adjustment to maintain sarcolemmal utrophin levels and subsarcolemmal mitochondrial gene expression in EDL muscles specifically. Additionally, PGC‐1α modulates other aspects of the sarcolemmal environment, including inducing critical components of the satellite cell niche fibronectin and tenascin C (73). Thus, enhanced local PGC‐1α activity may compensate for the lack of AMPK in administering the sarcolemmal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PGC-1 null satellite cells have a higher propensity for activation and proliferation [45]. …”
Section: Satellite Cellsmentioning
confidence: 99%